Max van Manen’s Phenomenology of Practice: Relation with Education Sciences and Philosophy - Kairė, Sandra (Problemos, 2021)
This paper investigates the method of the phenomenology of practice developed by the Canadian scholar Max van Manen. The paper describes the development and the main aspects of the phenomenology of practice as well as its importance and relevance to education sciences. However, in line with the critical remarks of the philosopher Dan Zahavi, the paper argues that there are fundamental problems with the phenomenology of practice in regard to phenomenology as philosophy. It is suggested that a researcher who applies this approach in his or her research should be cautious, critically evaluate van Manen’s presentation of phenomenology, and start his/her research from the phenomenological philosophy. Moreover, the paper argues that phenomenology should not be considered only as a methodological approach.
Keywords: Max van Manen; phenomenology of practice; education sciences; phenomenology; methodology